Effectively communicating comprehensive tumor genomic profiling results: Mitigating uncertainty for advanced cancer patients. Issue 2 (February 2022) - Bartley, Nicci; Best, Megan C.; Biesecker, Barbara B.; Fisher, Alana; Goldstein, David; Meiser, Bettina; Thomas, David M.; Ballinger, Mandy L.; Butow, Phyllis
Highlights: Advanced cancer patients experience diverse and fluctuating uncertainties. HCPs' co-ordination of care and communication can reduce uncertainties. Patients desire support from health professionals to disclose CTGP results to relatives to reduce their uncertainty. Abstract: Objective: To understand advanced cancer patients' experience of uncertainty when receiving comprehensive tumor genomic profiling (CTGP) results, and their perceptions of how healthcare provider (HCP) communication impacts uncertainty. Methods: Thirty-seven semi-structured interviews with advanced cancer patients were conducted within two weeks of patients receiving CTGP results. Transcripts were thematically analyzed, using an inductive approach. Results: We identified three themes that illustrate patient experience of uncertainties when receiving CTGP results: 1. Type and degree of uncertainty fluctuates along with changing illness circumstances and the nature of the CTGP results; 2. HCPs' co-ordination of care and communication shapes uncertainty, with immediate, clearer and simpler information promoting certainty; and 3. Patients felt that communicating results to reduce relatives' uncertainty is important, with patients choosing the time and process for achieving this and desiring HCPs support. Conclusion: Oncology patients are confronted with an array of uncertainties. Clear, simple communication from HCPs about results and their implications, and support to manage uncertainty, will be of benefit. Practice implications: If CTGP is to become routine clinical practice, clear communication will be crucial in reducing uncertainty. Awareness of potential uncertainties experienced by patients when receiving results, will assist HCPs to address uncertainties, reduce uncertainty where possible, and offer targeted support to patients struggling with uncertainty.